STRATEGI PEMASARAN DAN INOVASI PRODUK DALAM MENDORONG PERTUMBUHA UMKM BAMBU DI DESA JURANG JERO - nisa, Dwi karimatun; zulfa , Dina alawiyah; fauziyah , Intan; ningsih , Diana fitriah; lutfiyah , Hanim; intan , Diah ayu; ubudiyah , Azizah aziziyah (Kalam Nusantara Institute, 2024)
Bamboo is an all-purpose plant for most people in Indonesia. Apart from improving the land, balancing hydrology and global warming, bamboo can also provide high economic income. This is because, in the future, bamboo will become the world's main timber material. Bamboo is the material of the future, because from bamboo can be used as a variety of products ranging from food, building materials for household appliances to handicrafts such as plates, glasses, decorative lamp crafts, flower vases, and others. The method used in this research is ABCD (Asset Based Community Development), data sources are obtained from residents of jurang jero Village, gading District. Data collection techniques using documentation, observation, and interview techniques, while data analysis techniques by collecting data, reducing data, displaying data, and drawing conclusions. The purpose of this PKM activity is to provide assistance to bamboo craftsmen in jurang jero Village in utilizing bamboo plants so that the processing of bamboo plants is maximally varied and of higher quality in order to increase added value and economic value in jurang jero Village. The results of this PKM are 1) Increase community income, especially the jurang jero Village bamboo craftsmen group, gading sub-district, Probolinggo Regency, and regional income. 2) Increase the creativity of utilizing bamboo plants in jurang jero Village, gading District as handicraft materials. 3) Reducing unemployment. And 4) Empowerment of regional potential (bamboo plants).